Legal Protection for Victims of Revenge Porn: An Analysis from Thomas Aquinas’ Perspective on Criminal Law and Public Ethics - Henny Saida Flora; Mahfud Ramadhani (Journal of Strafvordering Indonesian, 2025)
The crime of revenge porn or the dissemination of intimate content without the victim's consent is a form of technology-based sexual violence that has a serious impact on human rights to privacy, honor, and dignity. This study uses a normative juridical method with a legislative and conceptual approach, relying on statutory analysis, doctrinal interpretation, and review of court decisions and scholarly literature to examine the consistency and effectiveness of legal protection frameworks. Through analytical interpretation of Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence (TPKS), Law No. 19 of 2016 concerning Electronic Information and Transactions (ITE), and Law No. 44 of 2008 concerning Pornography, the study critically evaluates how these regulations function substantively in protecting victims. The results of the study show that the normative provisions in the three laws are still overlapping and do not provide comprehensive protection for victims, particularly in distinguishing consensual and non-consensual content distribution, addressing secondary victimization, and ensuring victim recovery. From Thomas Aquinas' perspective, just law must contain a public moral dimension and be oriented towards bonum commune or the common good. Therefore, the reconstruction of legal protection for victims of revenge porn must be based on the integration of positive legal values and natural morality by strengthening punitive, preventive, and rehabilitative aspects. With such a legal model, the Indonesian legal system can realize substantive justice for victims, oriented towards restoring human dignity, and in line with the ideals of Pancasila law.